OPTIMIZATION OF MICROENCAPSULATION CONDITIONS OF TULIP PETAL ANTHOCYANIN: STORAGE STABILITY TEST - Karasu, S.; Sagdic, O.; Arici, M.; Kayacan, S. (PLAPIQUI(UNS-CONICET), 2020)
Tulip petals have the potential to be used as natural colorants due to their considerable anthocyanin content. In this study, anthocyanins from tulip petals were extracted and encapsulated by maltodextrin (MD) by using a spray drier. This study is the first attempt in the use of tulip anthocyanin as a natural colorant in the food model system. Encapsulation parameters, namely drying temperature (120 degrees C, 135 degrees C, 150 degrees C) and the ratio of the wall material (WM) to core material (CM) (1/1, 1/2, and 1/3) were optimized to obtain the maximum encapsulation efficiency (EE) of anthocyanin. The apple juice samples were colored with encapsulated anthocyanin and stored at different temperatures for 42 days to determine the degradation kinetic parameters of anthocyanin. EE value ranged from 93.06% to 97.07%. The optimum temperature and ratio of WM to CM were found as 134 degrees C and 1/3, respectively. Powder characteristics were determined by Scanning Electron Microscope (SEM). The powder particle samples obtained at the optimum experimental point showed a uniform distribution and did not contain cracks and holes. A significant change in a* values was observed at a temperature of 40 degrees C while the insignificant change was observed at 4 degrees C during 42 days storage period. Half-life value (t(1/2)) of the anthocyanin was found as 16.69-391.5 days. This study suggested that encapsulated tulip petal anthocyanin material should be stored at temperatures below 20 degrees C.
Keywords: Food colorants; degradation kinetic; SEM; RSM; SPRAY-DRYING MICROENCAPSULATION; DEGRADATION KINETICS; BIOACTIVE COMPOUNDS; L.; ENCAPSULATION; EXTRACTS; COLOR; ANTIOXIDANT; TEMPERATURE; Engineering